Tingkat Kepuasan Masyarakat Terhadap Pelayanan di Puskesmas Kecamatan Midai Kabupaten Natuna Tahun 2023 - Miranti Daswita; Nazaki Nazaki; Ardi Putra (Pusat Riset dan Inovasi Nasional, 2024)
Midai Health Center serves the community as well as public services in the health sector in general. However, there are several problems in public services at the Midai District Health Center, where the Midai District Health Center has never conducted a community satisfaction survey, there is a lack of competent human resources, slow service and a lack of supporting infrastructure. Therefore, this research aims to measure the level of community satisfaction at the Midai District Health Center, Natuna Regency. The method in this research uses a quantitative descriptive method using community satisfaction survey analysis with results in the form of numbers. The sampling technique used is Random Sampling. There are 9 indicators of community satisfaction surveys according to PERMENPAN No.14 of 2017, but in this study only 8 indicators were taken, namely requirements, service procedures, completion time, costs, type of service, implementer competency, implementer behavior, and infrastructure. The results of this research show that based on the calculation of the community satisfaction survey which refers to PERMENPAN No.14 of 2017, an index number was obtained for each service, namely general poly of 77.75, following dental poly of 80.75, then KIA and family planning poly of 79 .75 and finally the Inpatient Clinic, which is 78.50, is in the interval 76.61-88.30, so that overall the average value of public satisfaction with public services at the Midai District Health Center, Natuna Regency is 79.25 with the